A Randomized Phase II Trial of Adjuvant Hepatic Arterial Infusion and Systemic Therapy With or Without Panitumumab After Hepatic Resection of KRAS Wild-type Colorectal Cancer. Issue 2 (August 2021) - Kemeny, Nancy E.; Chou, Joanne F.; Capanu, Marinela; Chatila, Walid K.; Shi, Hongyu; Sanchez-Vega, Francisco; Kingham, Thomas Peter; Connell, Louise Catherine; Jarnagin, William R.; D'Angelica, Michael I.
Abstract : Objective/Background: The purpose was to determine whether adding Pmab versus no Pmab to an adjuvant regimen of hepatic arterial infusion (HAI) of floxuridine (FUDR) plus systemic (SYS) leucovorin, fluorouracil, and irinotecan (FOLFIRI) improves 15-month recurrence-free survival for patients with RAS wild-type colorectal cancer. Secondary endpoints included overall survival, toxicity, and influence of predictive biomarkers. Methods: This phase II trial randomized patients with K RAS wild-type resected colorectal liver metastases to adjuvant HAI FUDR + SYS FOLFIRI +/– Pmab (NCT01312857). Patients were stratified by clinical risk score and previous chemotherapy. Based on an exact binomial design, if one arm had ≥24 patients alive and disease-free at 15 months that regimen was considered promising for further investigation. Results: Seventy-five patients were randomized. Patient characteristics and toxicity were not different in the 2 arms, except for rash in +Pmab arm. Grade 3/4 elevation in bilirubin or alkaline phosphatase did not differ in the 2 arms. Twenty-five (69%; 95% CI, 53–82) patients in the Pmab arm versus 18 (47%; 95% CI, 32–63) patients in the arm without Pmab were alive and recurrence-free at 15 months. Only the Pmab arm met the decision rule, while the other arm did not. After median follow-up of 56.6 months, 3-year recurrence-free survival was 57% (95% CI, 43–76) and 42% (95% CI, 29–61), and 3-year overall survival was 97% (95% CI, 90–99) and 91% (95% CI, 83–99), +/– Pmab, respectively. Conclusions: The addition of Pmab to HAI FUDR + SYS FOLFIRI showed promising activity without increased biliary toxicity and should be further investigated in a larger trial. Abstract : Supplemental Digital Content is available in the text